Public relations mitigation: Using local wisdom to secure trust in private hospitals - Lestari, Eni; Rahmanto, Andre Noevi; Susanti, Ratna (PRofesi Humas, 2026)
Background: Public trust is a fundamental determinant of the reputation of private hospitals in a competitive healthcare environment. In this context, vulnerability to miscommunication can potentially lead to reputational crises. Previous research related to hospital public relations (PR) has focused on forms of crisis communication and media management. Meanwhile, research related to PR mitigation rooted in the local cultural context is still limited. This gap explores mitigation practices in private hospital PR by integrating local wisdom as a strategic communication method. Purpose: To analyze PR mitigation strategies based on local wisdom in building public trust in private hospital. Method: This research used a descriptive qualitative method to obtain data through in-depth interviews, including PR personnel, hospital management, and healthcare professionals in four private hospitals in Central Java. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, with the application of source triangulation to ensure validity. Results: Local wisdom values such as family-based communication, courtesy (unggah-ungguh), empathy (tepa slira), and mutual respect (nguwongne) inherent in Javanese culture served as the basis for the PR mitigation strategies. These values were applied when conveying information, handling complaints, and problem prevention practices, mitigating potential communication risks, reducing conflict escalation, and building emotional closeness between the hospital and the community. Conclusion: PR mitigation based on local wisdom played an important role in increasing public trust by strengthening relational communication and social legitimacy. Implication: Practically, this research emphasized the importance of integrating local cultural values into PR and health communication strategies to increase public trust. Theoretically, this research contributed to the analysis of PR and health communication by positioning local wisdom as a contextual mitigation framework in institutional communication within the health sector.